2013
DOI: 10.1080/02705060.2013.763296
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability in baseline δ15N and usage as a nutrient indicator in Lake Poyang, China

Abstract: Seasonal variation in nitrogen isotope ratios (d 15 N) of four baseline candidates belonging to the planktonic and benthic food webs of Lake Poyang, China, was investigated. These baseline candidates were particulate organic matter (POM), sediment organic matter (SOM), a filterer mussel (Corbicula flumine), and a grazer snail (Bellamya aeruginosa). d15 N values of POM and SOM varied significantly among the sampling seasons, while no significant seasonal variation was observed among the d15 N values of the muss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
4
11
0
Order By: Relevance
“…mussels) Cabana and Rasmussen, 1996;Harrington et al, 1998;Oczkowski et al, 2008;Carvalho et al, 2015). In addition and identical to our study, the range of δ 15 N values for nitrate and POM has been shown to be wider than the range for primary producers, indicating a timeaveraging effect in mussels (Gustafson et al, 2007;Wang et al, 2013). Previous studies reported mussel δ 15 N values between +6.6 and +16.7 ‰ in densely populated areas (Cabana and Rasmussen, 1996), polluted inland waterbodies (Wen et al, 2010;Wang et al, 2013), and a eutrophic estuary (Fry et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…mussels) Cabana and Rasmussen, 1996;Harrington et al, 1998;Oczkowski et al, 2008;Carvalho et al, 2015). In addition and identical to our study, the range of δ 15 N values for nitrate and POM has been shown to be wider than the range for primary producers, indicating a timeaveraging effect in mussels (Gustafson et al, 2007;Wang et al, 2013). Previous studies reported mussel δ 15 N values between +6.6 and +16.7 ‰ in densely populated areas (Cabana and Rasmussen, 1996), polluted inland waterbodies (Wen et al, 2010;Wang et al, 2013), and a eutrophic estuary (Fry et al, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…In addition and identical to our study, the range of δ 15 N values for nitrate and POM has been shown to be wider than the range for primary producers, indicating a timeaveraging effect in mussels (Gustafson et al, 2007;Wang et al, 2013). Previous studies reported mussel δ 15 N values between +6.6 and +16.7 ‰ in densely populated areas (Cabana and Rasmussen, 1996), polluted inland waterbodies (Wen et al, 2010;Wang et al, 2013), and a eutrophic estuary (Fry et al, 2011). Our values are at the lower end of this range, with mussel δ 15 N values in our study being between 6.8 and 10.3 ‰, indicating the estuary is not highly polluted by wastewater, agriculture or fertilizers.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, for our analysis, we assume that 3.4 % is appropriate. The baseline is the average d 15 N value of all snails collected at each sample site Aquat Ecol (2016) 50:187-195 189 (n = 3-10) because their isotopic signals are less variable in time as primary consumers (Post 2002b;Wang et al 2013), where the value 2 is the trophic position of the snail we using to estimate d 15 N base (Vander Zanden et al 1997;Post 2002b).…”
Section: Sample Collection and Stable Isotope Analysismentioning
confidence: 99%
“…Stable isotope technologies have been used as powerful and complementary tools for understanding the food web structure and energy pathways in aquatic ecosystems (Syvaranta et al 2011;Wang et al 2013). Both d 13 C and d 15 N can reveal the assimilated portion of consumers' diets at the time of synthesis (France 1995).…”
Section: Introductionmentioning
confidence: 99%